2010
DOI: 10.3892/or_00000806
|View full text |Cite
|
Sign up to set email alerts
|

Histological features of extratumoral breast lesions as a predictive factor of familial breast cancer

Abstract: Abstract. The aim of this study was to verify whether histopathological features of extratumoral and of primary tumor breast tissue could play a role in identifying patients with familial characteristics. We examined the clinicopathological features of 504 patients with sporadic or familial breast cancer stratified for risk of BRCA mutation. Patients with a higher risk of being carrier of BRCA gene mutations were significantly associated with tumor poor differentiation (p=0.003), positive lymph node invasion (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…In our study, BRCA noncarriers had denser interlobular stroma (SF grade 2/3) than BRCA carriers. Our findings are in agreement with those of Mangia et al, 59 which confirm that atrophy and fibrosis are associated with a lower mutation risk. Worsham and colleagues 60 demonstrated that fibrosis was protective against BC; in fact, women with fibrosis were at lower risk for BC progression than women without fibrosis.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In our study, BRCA noncarriers had denser interlobular stroma (SF grade 2/3) than BRCA carriers. Our findings are in agreement with those of Mangia et al, 59 which confirm that atrophy and fibrosis are associated with a lower mutation risk. Worsham and colleagues 60 demonstrated that fibrosis was protective against BC; in fact, women with fibrosis were at lower risk for BC progression than women without fibrosis.…”
Section: Discussionsupporting
confidence: 94%
“…We did not find any association between LT and higher mutation risk; however, study design may influence the interpretation of data that assessed LT after BC diagnosis (and consequently may not reflect LT prior to BC development). Mangia et al 59 examined the histopathological features of peritumoral and primary tumor breast tissue to assess mutation risk associated with BRCA1/2 genes. Among peritumoral lesions, only epithelial proliferative lesions were related to higher mutation risk in patients with familial BC (P = 0.003), and a significant difference in terms of high mutation risk was observed in usual ductal hyperplasia lesions (42% high-risk vs 17% lowrisk patients; P = 0.002).…”
Section: Discussionmentioning
confidence: 99%
“…Vascular invasion has been recently reported as a histoclinical parameter independently associated with poorer survival inside both basal and triple-negative breast cancer phenotypes [44,45]. However, in a our previous work, it has been demonstrated the predictive significance of the PVI for familial patients with BRCA gene mutation risk [27]. Thus, on the basis of our results, the PVI assessment might provide additional information on disease evolution of grade 2 tumors.…”
Section: Discussionmentioning
confidence: 50%
“…Of all tumors, 150 (80%) cases were invasive ductal carcinoma (IDC) not otherwise specified (NOS), with the remainder 37 (20%) consisting of other histological types including medullary, tubular, atypical medullary and lobular tumors. Assessment of the peritumoral vascular invasion (PVI) was based upon examination of sections stained with haematoxylin and eosin and was considered evident if at least one cohesive clump of tumor cells was clearly visible within peritumoral endothelial-lined spaces, both lymphatic channels and small blood vessels--closely associated with primary invasive carcinoma [27]. …”
Section: Methodsmentioning
confidence: 99%
“…The highly penetrant mutations in BRCA1 and BRCA2 account for small proportion of breast cancer cases [1]. These mutations were often associated with poor tumor differentiation, positive lymph node invasion, vascular peritumoral invasion [2], decreased expression of estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER2/Neu), and increased expression of p53 [3]. Certain breast cancer cases mimic this phenotype despite having wild BRCA1 due to low‐level promoter methylation of BRCA1 [4].…”
Section: Introductionmentioning
confidence: 99%